Peran Dimensi-Dimensi Entrepreneurial Marketing dalam Mendorong Kesuksesan Bisnis UMKM di Industri Ekonomi Kreatif - Setiyaningrum, Ari; Ramawati, Yussi (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2020)
This study aims to analyze the influence of entrepreneurial marketing dimensions, including proactiveness, opportunity-focused, risk-taking orientation, innovation-oriented, customer intensity, resource leveraging, and value creation of Small and Medium Enterprises (SME’s) business success in the creative economy industry. The study also examined the moderating role of company age on the entrepreneurial marketing dimension's influence on SME's business success. The study used survey methods by distributing questionnaires to 265 SME business owners in North Kalimantan. The sampling method uses nonprobability sampling with a convenience sampling technique. Data were analyzed using multiple linear regression analyses and moderated tests using the macro process of SPSS Hayes. The results of this study indicated that in the context of SMEs in the creative industry, customer intensity and value creation play a critical role in business success. Meanwhile, proactiveness, opportunity-focused, risk-taking orientation, innovation-oriented, and resource leveraging found no impact on SMEs' business success. The research also proves that the company's age moderated the impact of customer intensity on SME's success but does not moderate the influence of value creation to SME's business success.